Infratentorial ependymomas—a study of the centre in Katowice - Mandera, Marek (Childs Nerv Syst, 2015)
The aim of the study was to assess the correlation of the results of the treatment of infratentorial ependymomas with the degree of resection and histopathological diagnosis. The study was conducted on a group of 19 patients, 13 boys and 6 girls aged 3 months to 16 years, with infratentorial ependymoma treated at the Department of Paediatric Neurosurgery of the Medical University of Silesia in Katowice from January 2000 until December 2008. The most significant factor having an impact on overall survival and progression-free survival was totality of tumour resection. There has been no statistically significant influence of the histopathological type of ependymoma on the result of treatment. The tendency to report better results of treatment of non-anaplastic ependymoma seems to derive from a statistically higher frequency of total removal of tumours of this type.